Administration of physical education and sport programs - Horine, Larry (McGraw-Hill, 2004)
This undergraduate text presents the theory and practice of the administration of physical education and sport programs in an easy-to-read, easy-to-use format. With a strong background in history, Administration of Physical Education and Sport Programs addresses current topics and trends in management and administration, while investigating the future of athletic administration. With general topics covering the basics of management and administration, to more topic specific chapters discussing public relations, communications and law, this text covers everything students need for administration courses